Climate change affects Galliformes taxonomic, phylogenetic and functional diversity indexes, shifting conservation priority areas in China - Wang, Bin; Ye, Weijia; Xu, Yu; Zhong, Xue; Zhang, Jindong; Yang, Nan; Yang, Biao; Zhou, Caiquan (Diversity & distributions, 2023)
Aim Comprehensive biodiversity protection necessitates the consideration of multiple indexes of diversity, and how the distribution patterns of priority areas may shift under climate change. Galliformes is a globally endangered avian order vulnerable to climate change that provide an important indicator for wildlife conservation effectiveness. Here, we identified priority areas for conserving Galliformes taxonomic, phylogenetic, and functional diversity in China and their spatial dynamics subject to climate change, and examined how well existing protected areas align with current and future priority areas. Location China. Methods We applied species distribution modelling and Zonation algorithms to identify conservation priority area dynamics for 47 galliform species across three biodiversity indexes subject to three future climate change scenarios to 2050s and 2070s. We overlaid these identified priority areas onto existing national nature reserves and national parks to assess and project their effectiveness. Results Current priority areas proved spatially incongruent between indexes, with an optimal area overlap comprising just 10.3% of China's land area, lying largely outside of existing protected areas. Furthermore, over 80% of modelled optimal priority areas currently lacked formal conservation status. Future priority areas will shift substantially under climate change, to an extent dependent on greenhouse gas emission scenarios. Nevertheless, we identified five large regions where optimal Galliformes diversity indexes should remain stable under all scenarios, thus providing potential climatic refugia, if protected from human encroachment. Main Conclusions The current deficits we identified for Galliformes protection in China resonate with a broader need for hierarchical conservation strategic planning across regions and ecosystems to ensure long‐term biodiversity protection, accommodating for climate change.